Korelasi antara Skor ICH C-Reactive Protein, D-Dimer terhadap Luaran Pasien Perdarahan Intraserebral - Irina, Rr Sinta; Indharty, Rr Suzy (Jurnal Neuroanestesi Indonesia, 2023)
Latar Belakang dan Tujuan: Perdarahan intraserebral (Intracerebral hemorrhage/ICH) merupakan 10% hingga 15% dari semua stroke dan memiliki angka mortalitas dan morbiditas yang tinggi di dunia. Skor ICH valid untuk memprediksi derajat keparahan pasien perdarahan intraserebral yang dirawat di ICU. Kenaikan nilai C-reactive protein (CRP) menjadi prediktor terhadap hasil luaran pasien ICU. Tujuan penelitian adalah untuk mengetahui korelasi skor ICH, CRP dan D-dimer terhadap hasil luaran pada pasien perdarahan intraserebral.Subjek dan Metode: Subjek penelitian merupakan 27 orang pasien perdarahan intraserebral yang dirawat di ICU RSUP H. Adam Malik dan Rumah sakit Universitas Sumatera Utara. Pengambilan data secara consecutive sampling, kemudian diukur skor ICH, CRP, D-dimer dan dianalisa pemeriksaan tersebut dengan lama perawatan.Hasil: Dari total 27 pasien, 22 (81,5%) pasien pindah ruang rawat dan 5 (18,5%) pasien meninggal dunia. Rerata untuk skor ICH 2,70(0,67), CRP 1,41(0,72), dan D-dimer 2757,96(1230,73). Hasil korelasi antara skor ICH dengan lama rawatan dijumpai korelasi positif (r = 0,498; p = 0,008), didapatkan korelasi lemah antara CRP dengan lama rawatan (r = 0,315; p = 0,109) dan korelasi antara D-dimer dengan lama rawatan dan dijumpai korelasi positif (r = 0,546; p = 0,003).Simpulan: Didapati skor ICH, CRP dan D-dimer memiliki pengaruh terhadap lama rawatan pasien dengan perdarahan intraserebralCorrelation between ICH Score, C-Reactive Protein and D Dimer on the outcome of Intracerebral Hemorrhage PatientsAbstractBackground and Objective: Intracerebral hemorrhage (ICH) accounts for 10% to 15% of all strokes and has a high mortality and morbidity rate in the world. The ICH score is valid for predicting the severity of intracerebral hemorrhage patients treated in the ICU. The increase in C-reactive protein (CRP) value is a predictor in the outcome of ICU patients. The aim of this study was to find out how the ICH, CRP and D-dimer scores correlated with the outcome in intracerebral hemorrhage patients.Subjects and Methods: The subjects of this study were 27 patients with intracerebral hemorrhage who were treated in the ICU of H. Adam Malik Hospital and the University of North Sumatra Hospital. Data were collected using consecutive sampling, then ICH, CRP, D-dimer scores were measured and the examination was analyzed by length of stay.Results: Out of a total of 27 patients, 22 (81.5%) patients moved to the ward and 5 (18.5%) patients died. The mean for ICH score was 2.70(0.67), CRP was 1.41(0.72), and D-dimer was 2757.96(1230.73). The results of the correlation between ICH score and length of stay found a positive correlation (r = 0.498; p = 0.008), a correlation between CRP and length of stay had a weak correlation (r = 0.315; p = 0.109) and a correlation between D-dimer and length of stay and found a correlation positive (r = 0.546; p = 0.003).Conclusion: It was found that ICH, CRP and D-dimer scores had an effect on the length of stay of patients with intracerebral hemorrhage